2016
DOI: 10.1177/1071100716674309
|View full text |Cite
|
Sign up to set email alerts
|

MRI Quantification of the Impact of Ankle Position on Syndesmosis Anatomy

Abstract: Level III, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
1
3
1
1
Order By: Relevance
“…These findings are in contrast to the results of Nault et al in an MRI-study of intact non-weight bearing ankle joints [27]. The published results show significant differences of tibiofibular distances and fibula rotation depending on dorsi- and plantarflexion.…”
Section: Discussioncontrasting
confidence: 90%
“…These findings are in contrast to the results of Nault et al in an MRI-study of intact non-weight bearing ankle joints [27]. The published results show significant differences of tibiofibular distances and fibula rotation depending on dorsi- and plantarflexion.…”
Section: Discussioncontrasting
confidence: 90%
“… 38 However, these conclusions were based off the restoration of ankle ROM, and not syndesmotic reduction. In addition to this study, Nault et al 29 demonstrated increases in syndesmotic width with ankle plantarflexion, as did Kortekangas et al, 18 who performed intraoperative CT scans and detected 7 malreductions out of 21 cases after flexible fixation. In these cases, open exploration was performed intending to revise the reduction, but each ankle was found to be well reduced under direct inspection and on subsequent CT scans at 0 degrees dorsiflexion.…”
Section: Discussionsupporting
confidence: 63%
“…Prior literature suggested that over-compression is not possible in the setting of a reduced fibula and dorsiflexed ankle; this has likely perpetuated the false notion of safety when forcefully clamping across the syndesmotic axis. 42 Due to the dynamic movement of the distal tibiofibular articulation with ankle range of motion, 43 overcompression may carry significant clinical implications. In our study, manual digital pressure was sufficient to provide the appropriate amount of force to overcome syndesmotic instability without demonstrating any degree of overcompression.…”
Section: Discussionmentioning
confidence: 99%